Comprehensive analysis of mutations of renal cell carcinoma in an autosomal dominant polycystic kidney disease patient. Issue 19 (May 2020) - Shim, Kwang Eon; Lee, Chung; Kim, Jin Up; Choi, Gwang Ho; Kwak, Kyoung Min; Kim, Seok Hyung; Kim, Hyunho; Yoon, Jong Woo; Shin, Tae Young; Jeong, Chang Wook; Kim, Hyunsuk
Abstract : Abstract: Renal cell carcinoma (RCC) is known to be more prevalent in autosomal dominant polycystic kidney disease (ADPKD) patients than in the general population. However, little is known about genetic alterations or changes in signaling pathways in RCC in patients with ADPKD. In the current report, whole-exome and transcriptome sequencing was performed for paired samples of tumor tissue, cyst tissue, and peripheral blood (triple set) from a patient diagnosed with ADPKD and RCC. A 68-year-old man with ADPKD underwent left partial nephrectomy and was diagnosed with RCC. DNA and RNA were extracted from the triple set of the patient. A nonsense mutation in PKD2 (p.Arg742X), which is well known as a pathogenic variant in ADPKD, was identified in the paired triple set. In the tumor sample, a somatic missense mutation of VHL (p.S65L) was found, which is known as a pathogenic mutation in Von Hippel-Lindau syndrome and RCC. Furthermore, loss of chromosome 3p, where VHL is located, was detected. Upregulated VEGFA was found in the analysis of RCC mRNA, which might be caused by the loss of VHL and accelerate angiogenesis in RCC. Proliferation was also expected to be activated by the MAPK signaling pathway, including NRAS and MAPK1 expression. Abstract : Supplemental Digital Content is available in the text